Ungkapan marah dalam komunitas marah-marah di media sosial X (kajian sosio-pragmatik) - Nova, Indah Fauziah; Winarti, Daru (Universitas Mulawarman, 2024)
Language is a medium for expressing anger. The ease of communication on social media encourages speakers to form virtual communities that specifically designed for expressing anger. The Angry Community on X is an example of how language is used to express emotions on social media. This paper aimed to examine how anger is conveyed through language. This paper was a qualitative descriptive method using a case study approach. The data consist of 30 expressions of anger obtained from tweets or threads posted by members of the Angry Community. Data were collected over one month, specifically in August 2024. The results showed that swear words and locutionary speech act were used to express anger. References to the meanings of swear words are categorized into 27% situational terms, 53% related to animals, 7% affiliated to spirits, and 13% associated with objects. The sentence structures identified included 19 declarative sentences, 6 interrogative sentences, and 5 imperative sentences. Members of the community are predominantly male, aged between 16 and 25 years, with the majority having completed their education at senior high school. In contrast, community members have diverse occupations, equally split between private sector employees and entrepreneurs.